تحليل طريقة الإملاء في تدريس مهارة الكتابة لطلاب الصف السابع في معهد نور الحكيم للتربية الإسلامية الحديثة في تنبونج - Siregar, Eka Rahma Ainun; Zulheddi, Zulheddi (YASIN, 2025)
This research aims to optimize the application of the imla' method in learning maharah kitabah in class VII of the Nurul Hakim Modern Islamic Boarding School in Medan. Qualitative methods are used by conducting observations and interviews with students and teachers to understand the impacts and challenges of implementing the imla' method. The research results show that the imla' method is able to increase the accuracy of writing letters, introduce new vocabulary, and train students' concentration. However, there are several obstacles such as differences in student abilities, lack of variety in delivery methods, and time constraints that affect the effectiveness of learning. From interviews with teachers, it was found that grouping students based on ability and using varied learning media could help overcome these challenges. Thus, this research recommends the implementation of additional strategies to increase the effectiveness of the imla' method in learning maharah kitabah in Islamic boarding schools.